Near-infrared responsive gecko-inspired flexible arm gripper. (December 2022) - Luo, Xiaohang; Dong, Xiaoxiao; Zhao, Hong; Hu, Travis Shihao; Lan, Xiuping; Ding, Lan; Li, Jiapeng; Ni, Huiqin; Contreras, Jordan A.; Zeng, Hongbo; Xu, Quan
Abstract: Inspired by the microstructure of gecko toes, a drivable bionic gecko toe adhesion surface with double-layer structure was designed and fabricated. The driving ability is derived from the volume shrinkage of the dehydrated hydrogel after the driving hydrogel layer is irradiated by near-infrared light (808 nm) (the temperature of the single-layer hydrogel can be increased from 17.9 °C to 107 °C within 30s, and the curling angle can be curled by 0°–180°, similar to the folded state.), and another layer with a microstructure similar to gecko toes can withstand a maximum shear force of 22.4N/cm −2 . The different properties of the two layers are combined together to achieve a reversible transition of adhesion/desorption similar to the gecko walking process. The double-layer structure of the drivable bionic gecko toe adhesion surface was structurally optimized to prepare a four-arm gripper that could grasp/release only by unilateral irradiation. This bilayer-structured bionic gecko toe adhesion surface has great design potential, and in the future, it is hoped that it can provide insights into the preparation of large-actuated remote-controlled robots and fast-actuated soft robots. Graphical abstract: Image 1 Highlights: Surface GFe of the gecko-like seta micropillar array with the optimized Fe3 O4 gradient distribution and the shear force up to 22.4 N/cm −2 was prepared with PDMS as the base material. Hydrogel (p(AAm-co-NIPAAm-co-TA)-Fe) with fast response to near-infrared light-driven properties was designed, and the temperature transition from 17.2 °C to 107 °C was achieved by infrared irradiation for 30 s. Realize drive folding from 0° to 180°. Heterointerfaces with different hydrophilic/hydrophobic properties were combined to prepare a double-layer gecko-like seta micropillar array surface with both infrared driving and long-term adhesion properties. Adjust the surface of the double-layer imitation gecko seta micropillar array. An ingenious four-arm gripper structure was designed, which can grasp/release objects within 4 min by irradiating only one side.